1973
DOI: 10.1007/bf02403532
|View full text |Cite
|
Sign up to set email alerts
|

Structure of rapidly solidified aluminium-silicon alloys

Abstract: This paper present results obtained on rapid solidification of aluminium-silicon alloys from the liquid state. It shows that the limit of primary solid solubility is extended almost to the eutectic composition and that the large supersaturation is relieved on raising the annealing temperature to the range 110 to 450~ This conclusion is based on measurements of lattice parameter and is also supported by corresponding changes in hardness and metallographic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 9 publications
4
12
0
Order By: Relevance
“…Significant changes in hardness occur and are attributed to changes in the microstructure. Similar correlations between the microstructure and hardness were made with Al-Si and Al-Ni series alloys [5,6,18,[23][24][25]36,37]. On the other hand, intermetallic crystallization contributed to an improvement to the hardness at the expense of its ductility [36][37][38].…”
Section: Changes In Microhardnesssupporting
confidence: 50%
See 1 more Smart Citation
“…Significant changes in hardness occur and are attributed to changes in the microstructure. Similar correlations between the microstructure and hardness were made with Al-Si and Al-Ni series alloys [5,6,18,[23][24][25]36,37]. On the other hand, intermetallic crystallization contributed to an improvement to the hardness at the expense of its ductility [36][37][38].…”
Section: Changes In Microhardnesssupporting
confidence: 50%
“…In this study, the mechanical properties of rapidly solidified ribbons and their ingot counterparts were determined by Vickers microhardness measurements. As performed in preceding literature studies [13][14][15][16][17][18][19][20][21][22][23][24][25]36,37], we first used one applied load (0.098 N) to measure the Vickers hardness value (H V ) of both ingot and melt-spun specimens. The values were calculated using the standard Vickers formula,…”
Section: Changes In Microhardnessmentioning
confidence: 99%
“…Careful examination of the alloy side showed that Si (produced from silica reduction) has reacted with Al to form dendrites (marked A) similar to those observed in other studies. [46,47] The Si concentration in the dendritic region varies from 40 to 60 pct. Furthermore, some regions in the alloy side show very high Si concentration (>90 pct), which can be distinguished as plates (marked B).…”
Section: Resultsmentioning
confidence: 99%
“…The form of Si changes according to the cooling rate, such as quench modification, thermal modification, or chemical modification [45]. Rapid cooling decreases the amount of Si ejected into the liquid by extending its solubility in Al [46], so ɑ-Al solidifies first in the preferential cellular structure leaving the residual Si at the boundaries [47].…”
Section: Discussionmentioning
confidence: 99%